1994
DOI: 10.1007/bf02088356
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and pathology of radiation-induced esophagitis

Abstract: Radiation-induced esophagitis can cause substantial morbidity. Experiments in lab animals have shown that pretreatment with indomethacin protects the esophagus from radiation damage. We conducted a prospective, double-blind, randomized trial of naproxen vs placebo in patients undergoing thoracic radiation therapy for lung cancer. Twenty-eight patients were enrolled, of which 26 completed the study. Sixteen patients were given a short course of radiation (30 Gy/10 fractions/2 weeks), and 10 patients were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A placebo-controlled trial, however, did not show a beneficial effect [13]. For nonsteroidal anti-inflammatory drugs like indomethacin or naproxen a prophylactic effect is not proven either [15,20]. Likewise, several randomized phase II and III studies of amifostine have demonstrated mixed results regarding its ability to reduce esophagitis [4,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A placebo-controlled trial, however, did not show a beneficial effect [13]. For nonsteroidal anti-inflammatory drugs like indomethacin or naproxen a prophylactic effect is not proven either [15,20]. Likewise, several randomized phase II and III studies of amifostine have demonstrated mixed results regarding its ability to reduce esophagitis [4,9].…”
mentioning
confidence: 99%
“…In 16% of the patients a Candida infection was found with a comparable incidence in both groups. Soffer et al performed endoscopy with esophageal biopsies and brushings before and at the last day of thoracic radiotherapy with 30-50 Gy in 26 patients [20]. 17 patients showed significant deterioration of their histological lesions regarding esophagitis.…”
mentioning
confidence: 99%
“… 1)Radiation‐induced esophageal diseases are usually induced by thoracic neoplasm radiotherapy, particularly radiation treatment for lung cancer. [ 130–133 ] It can result in dysphagia, odynophagia, heartburn, and chest pain, which may even require temporary interruption of treatment under severe circumstances. [ 132 ] The mainstream route for the nanomaterial design of radiation‐induced esophagus disease treatment is nanocarrier‐associated gene therapy.…”
Section: Nanomaterials Design For Prevention and Treatment Of Various mentioning
confidence: 99%
“…[ 130–133 ] It can result in dysphagia, odynophagia, heartburn, and chest pain, which may even require temporary interruption of treatment under severe circumstances. [ 132 ] The mainstream route for the nanomaterial design of radiation‐induced esophagus disease treatment is nanocarrier‐associated gene therapy. MnSOD‐plasmid/liposome complex is a typical representative, which uses plasmid/liposome to transfer MnSOD into the esophagus.…”
Section: Nanomaterials Design For Prevention and Treatment Of Various mentioning
confidence: 99%
“…Currently, there are no evidence-based guidelines to prevent esophagitis. Some reports attest that sucralfate might be useful to reduce radiation-induced esophagitis [8, 9], but a placebo-controlled trial did not confirm its effectiveness [10], and no prophylactic effect has been proven for nonsteroidal anti-inflammatory drugs [11, 12]. Moreover, several randomized phase II and III studies of amifostine have shown conflicting results in reducing esophagitis [13, 14].…”
Section: Introductionmentioning
confidence: 99%